Assessing the potential of black soldier fly larvae meal to replace commercial protein concentrates in broiler diets effects on efficiency, economic values, and internal organs - Tarek Ibrahim Majeed; Qutaiba Jassim Gheni; Jaffer Mohammed Jassim (Acta Scientiarum. Animal Sciences, 2025)
This study examines the ideal incorporation of black soldier fly larvae (BSFL) in broiler diets, optimizing animal performance while fostering a sustainable food system. Protein utilization, digestion, production efficiency, economic viability, and the development relative weights of internal viscera are evaluated to determine the ideal inclusion level of BSFL. The experiment was conducted in the University's poultry facility. A total of 225-day-old unsexed Ross 308 chicks were randomly allocated to five treatments for 35 days. The treatments substituted imported protein concentrate with BSFL meal at doses of 0, 25, 50, 75, and 100%. The findings indicated that treatments including elevated proportions of BSFL meal (50, 75, and 100%) markedly enhanced the apparent digestibility coefficient (ADC) in comparison to the control, yielding values of 77.48, 77.40, and 77.92%, respectively. Nevertheless, no substantial variations were detected in the protein efficiency ratio (PER) across the treatments. The maximum inclusion level of BSFL (100%) led to an improvement in the economic efficiency index (1087.35) relative to the control (1534.12), as illustrated in Table 3. The decline in the economic efficiency index indicates a decrease in feed costs, which enhances the whole manufacturing process by increasing cost-effectiveness. No substantial disparities in mortality rates persisted uniformly across all treatments. Although notable variances existed among treatments, T5 had the most productive index. No significant variations were seen in the relative weights of internal organs between the treatments, suggesting that BSFL meal did not adversely affect organ development (Table 4). The statistical analysis indicated no significant variations among the experimental treatments regarding the relative weights of the heart, liver, stomach gland, gizzard, cecum, spleen, Fabrician gland, and index gland. In conclusion, BSFL meal demonstrates potential as a cost-efficient and sustainable substitute for imported protein concentrates in broiler diets, with the appropriate inclusion level combining performance enhancements and economic advantages.